Measles Vaccine Failure OR Emergence of New Virus strain: 2018 Measles Outbreak Peshawar, Pakistan - Khattak, Ayesha (International Journal of Pathology, 2023)
Introduction: Measles vaccines are included in routine immunization programs started in 19784 but still, a large number of cases have been reported in the recent past across the country Objective: The frequency and genotypes of measles Virus (MeV) in children vaccinated against Measles Virus (MeV) were investigated through PCR using gene-specific primers during the 2018 measles outbreak in Peshawar, Pakistan. Methodology: Throat swabs and urine samples, as well as clinical and demographic data, were collected from 156 children with measles-like symptoms, admitted to different tertiary care hospitals in Peshawar. Results: Most prevalent genotypes found were D3, G2, and B3.1. The distribution of MeV genotypes was statistically significant in unvaccinated children (p<0.005). Mixed genotypes (D3 and D7) were identified in 2.45% of children administered with single or double dose and 14.7% of the samples were not typed viz in Clade-D (7.4%), Clade- B (4.1%), and Clade- G (3.3%). The predominant genotype found in vaccinated and unvaccinated children was D3 followed by B3.1 and G2. Most of the children were found positive for MeV of age 1-5 years and the notable complications were severe pneumonia (5.6%) and diarrhea (26.8%). Furthermore, MeV and Rubella Virus (RV) coinfection was found in 6.4% of the total children, especially in unvaccinated children of the study. Conclusion: It is concluded that MeV genotype D3 was prevalent in the study population, importantly in the vaccinated children. Moreover, a substantial number of un-typed samples seem the emergence of new variants.